A CRITIC-VIKOR based robust approach to support risk management of subsea pipelines. (July 2022) - Li, Xinhong; Han, Ziyue; Yazdi, Mohammad; Chen, Guoming
Abstract: The risk factors related to subsea pipeline failure are diversified and dependent. Efficient risk management is critical for preventing subsea pipeline failure accidents. This paper presents a novel approach for effective risk management of subsea pipelines, which can extract the importance of pipeline risk factors and prioritize the risk management of subsea pipelines. This approach integrates CRITIC with VIKOR to capture the internal correlation and inconsistency among pipeline risk factors and accurately quantify the risk of different pipe sections. The pipeline safety factors are identified to build index-based risk evaluation system of subsea pipelines. The failure risk of subsea pipeline varies with the pipe sections, which is divided considering the structural conditions of pipeline and environmental conditions. The CRITIC method is utilized to assign the weight of risk indices, and the VIKOR method is applied to assess the importance of pipe sections in a Multiple criteria decision-making (MCDM) manner, which can help to find the weaknesses of the pipeline and decide the risk of which pipe section should be mitigated prior. A case study is performed to illustrate the application of the proposed methodology, and it is observed that the approach can be a valuable tool to support more effective risk management and decision-making of subsea pipelines.